2007
DOI: 10.1136/hrt.2006.099739
|View full text |Cite
|
Sign up to set email alerts
|

Parallel stenting using two sirolimus-eluting stents in an ectatic coronary artery stenosis

Abstract: 5 Sitbon O, Badesch DB, Channick RN, et al. Effects of the dual endothelin receptor antagonist bosentan in patients with pulmonary arterial hypertension: a 1-year follow-up study. Chest 2003;124: 247-54. 6 Channick R, Simonneau G, Sitbon O, et al. Effects of the dual endothelin-receptor antagonist bosentan in patients with pulmonary hypertension: a randomized placebo controlled study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Stefanadis et al has reported superior outcomes covered stents for sealing of coronary aneurysm as compared to bare metal stent [12]. Drug-eluting stent reduces the rate of re-stenosis but due to larger vessel diameter in ectatic coronary artery disease, it is generally not used in this clinical condition [6] [13]. However, Rha et al has reported successful implantation of two drug-eluting stents parallel to each other in ectatic LAD artery [13].…”
Section: Discussionmentioning
confidence: 99%
“…Stefanadis et al has reported superior outcomes covered stents for sealing of coronary aneurysm as compared to bare metal stent [12]. Drug-eluting stent reduces the rate of re-stenosis but due to larger vessel diameter in ectatic coronary artery disease, it is generally not used in this clinical condition [6] [13]. However, Rha et al has reported successful implantation of two drug-eluting stents parallel to each other in ectatic LAD artery [13].…”
Section: Discussionmentioning
confidence: 99%
“…Stefanadis et al reported the successful deployment of an autologous venous graft-covered stent to a coronary aneurysm 9. Rha et al reported a challenging case of "parallel stenting" in which two 3.5×180-mm sirolimus-eluting stents were used in parallel to each other in a patient with CAE with IVUS guidance 10. In a literature review of the management of CAE cases, we found no standard treatment option or long-term follow-up results with revascularization therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical revascularization is also recommended in such situation. With the help of intravascular ultrasound, percutaneous intervention could be performed safely with adequate vessel assessment [13]. …”
Section: Discussionmentioning
confidence: 99%